Interaction of C-terminal p53 isoforms depends strongly upon DNA sequence and topology - Goswami, Pratik; Šislerová, Lucie; Dobrovolná, Michaela; Havlík, Jan; Šťastný, Jiří; Brázda, Václav (Biochimie, 2023)
The p53 protein is a key tumor suppressor and the most commonly mutated and down-regulated protein in human tumors. It functions mainly through interaction with DNA, and p53 acts as a transcription factor that recognizes the so-called p53 target sites on the promoters of various genes. P53 has been shown to exist as many isoforms, including three C-terminal isoforms that are produced by alternative splicing. Because the C-terminal domain is responsible for sequence-nonspecific binding and regulation of p53 binding, we have analyzed DNA recognition by these C-terminal isoforms. Using atomic force microscopy, we show for the first time that all C-terminal isoforms recognize superhelical DNA. It is particularly noteworthy that a sequence-specific p53 consensus binding site is bound by p53α and β isoforms with similar affinities, whilst p53α shows higher binding to a quadruplex sequence than both p53β and p53γ, and p53γ loses preferential binding to both the consensus binding sequence and the quadruplex-forming sequence. These results show the important role of the variable p53 C-terminal amino acid sequences for DNA recognition.
Keywords: nádorový supresorový protein p53; alternativní sestřih; protein - isoformy; DNA; Protein Isoforms; Humans; sekvence nukleotidů; Base Sequence; lidé; Alternative Splicing; Tumor Suppressor Protein p53